Immune checkpoint inhibitor-associated diabetes mellitus: mechanisms, clinical manifestations, and management strategies - Chen, Yu; Wang, Xiaolu; Duan, Shuyun (Frontiers in Endocrinology, 2026)
Immune checkpoint inhibitor–associated diabetes mellitus (ICI-DM) is a rare but life-threatening endocrine immune-related adverse event characterized by abrupt insulin deficiency and a high incidence of diabetic ketoacidosis (DKA). Unlike classical type 1 diabetes, ICI-DM often develops after only a few treatment cycles, shows a fulminant phenotype with disproportionally modest HbA1c elevation, and is typically irreversible and glucocorticoid-refractory, necessitating permanent insulin therapy. Mechanistically, PD-1/PD-L1 blockade disrupts pancreatic immune tolerance and permits autoreactive CD8+ T-cell–mediated β-cell destruction, with risk amplified by susceptible HLA haplotypes and pre-existing islet autoantibodies (most commonly GAD antibodies). Additional contributors include pancreatic inflammation, cytokine-driven immune activation, incretin axis perturbations (GLP-1/GIP), and β-cell dedifferentiation programs. Clinically, timely recognition requires proactive glucose monitoring, early ketone assessment, and evaluation of C-peptide and pancreatic enzymes, particularly because DKA can occur rapidly after symptom onset. This review synthesizes current evidence on ICI-DM epidemiology, pathogenesis, clinical presentation, and management, and discusses emerging preventive and disease-modifying strategies, including mesenchymal stromal cells and B-cell–targeted approaches, to optimize outcomes in patients receiving immunotherapy.